Stereoselective Synthesis of (Z)‐Dihomoallylic Phosphonates with Quaternary Carbon Center by Palladium‐Catalyzed Bisallylation of Vinylethyene Carbonates with β‐Ketophosphonates. Issue 4 (24th February 2021) - Liu, Zhigang; Ke, Miaolin; Zhang, Ke; Zuo, Sheng; Jiang, Meifen; Chen, Fener
Abstract: A palladium‐catalyzed bisallylation of vinylethylene carbonates with β ‐ketophosphonates to access to ( Z )‐trisubstituted dihomoallylic phosphonates bearing a quaternary carbon center with good regio‐ and stereoselectivity is reported. This operationally simple protocol exhibits excellent functional group tolerance to deliver valuable dihomoallylic phosphonates. Abstract : Palladium‐catalyzed bisallylation of vinylethylene carbonates with β ‐ketophosphonates is reported to access to (Z)‐trisubstituted dihomoallylic phosphonates bearing a quaternary carbon center with good regio‐ and stereoselectivity. This operationally simple protocol exhibits excellent functional group tolerance to deliver valuable dihomoallylic phosphonates.